(untitled) (International Journal of Food and Nutritional Sciences, 2019)
In this work, a new asymmetric CPW feed double square patch antenna is designed and simulated using an electromagnetic solver for applications in wireless bandwidth. The planar asymmetric CPW horizontal surface (Conventional coplanar waveguide) combined with a double square patch antenna